Development of inhibitors in haemophilia - Serban, M.; Mihailov, D.; Pop, L.; Ionita, H.; Ursu, E.; Talpos-Niculescu, S.; Ritli, L.; Baghiu, D.; Uscatescu, V.; Petrovanu, C.; Stancu, P.; Savescu, D.; Cucuianu, A.; Schramm, W. (Hämostaseologie, 2011)
A number of 513 consecutive patients (494-haemophilia A and 19-haemophilia B) from eight haemophilia treatment centers have been investigated with Bethesda assay for the presence of factor VIII or IX inhibitors. The overall prevalence of inhibitors was 15.20%, 18.48% in severe, 5.60% in moderate and 12.24% in mild forms. The prevalence was higher than reported in most of the western countries. The age at start of substitution (p = 0.9775), the frequent switching of factor concentrates (p = 0.8931) were not relevant factors for the development of inhibitors. It is worth to be mentioned the unexpectedly occurrence of inhibitors in prior inhibitor negative (6/72) patients (during surgical interventions) probably due to their previous scarce substitution, occurrence which seems not being connected with the continuous infusion modality of factor VIII administration (p = 0.8341). In controversial situations, in the field of low titer (≤1 BU/ml) inhibitors for a reliable interpretation of the results the performance of recovery index and half-life time assessment of FVIII/IX was undertaken.
Keywords: Haemophilia; inhibitors